Expanding language development children in elementary school age - Miranti Miranti; Anik Purwanti (PROCEEDING UMSURABAYA, 2020)
Abstract.Language and communication skills are critical to a child's development. Goodcommunication makes them able to engage in socialization as well as others from formal classroom instruction and the environment around them. Active communication involves both speech and language. Speech is a means of verbal communication to convey desire goals, and language is using shared rules to put words together to express thoughts and feelings. To be a good speaker the child‘s must have extensive language knowledge and always develop according to where they are. The success of a child‘s to be able to interact in a social relationship is judged by how they estabilish communication with people in their surroundings. When a child begins to engage in social relationship with those around him, then that is the right time for children to develop their language skills. For children in When children learn in a class, the teacher must be able to create an interactive, communicative, and fun learning atmosphere. With interactive, communicative, and fun learning atmosphere in the classroom will make children interested in actively involved directly in learning activities, thus forcing them to develop their language.Keyword: Children, Language, Development.